Tasks of defence planning under martial law in Ukraine - Voloshchuk, Vadym (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article states the need to increase the efficiency of the Government of Ukraine’s actions in the field of defence, the role of the Minister of Defence of Ukraine in wartime and strengthening the institutional capacity of the Ministry of Defence of Ukraine. The article reveals the achievements and problems of regulatory and legal support of defence planning in the context of military conflict in Ukraine. Defence planning involves the development, approval and adoption of plans that reflect specific measures, methods, means, as well as the timing and main executors of the relevant measures. The author formulates a number of proposals for solving serious legal and organisational problems in the field of defence planning under martial law in Ukraine. Attention is focused on the need to abandon the development of medium- and long-term defence plans and to revise the Military Security Strategy of Ukraine and the Strategic Defence Bulletin of Ukraine. Based on the testing of foreign experience, publish an information and analytical journal «White Paper on Defence of Ukraine». It is necessary to prepare and amend legislation to specify the content of the defence plan in the context of martial law and repulsion of armed aggression in Ukraine.